2020
DOI: 10.21203/rs.3.rs-26244/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Travelling and COVID-19: A Mathematical Model

Abstract: A non-linear mathematical model is proposed to study the impacts of travelling in human-human transmission of COVID- 19.Two different regions are considered and transmission dynamics of COVID-19 dissemination in two regions caused by travelling from one region to other and infection during travel are discussed.Besides contacts between susceptible and infected population of a region off the travel,transmission of disease due to contacts during travel is also considered.The proposed model is analysed using stabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Meanwhile, high income levels likely increase the mobility and number of contacts, which increases the rate of new cases and deaths ( 16 ). In addition, traveling and population dispersal can aggravate the spread of disease in each region ( 17 , 18 ). Although air travel has clearly been a major driver of the pandemic, intercontinental travel restrictions were less effective between Europe and the USA ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, high income levels likely increase the mobility and number of contacts, which increases the rate of new cases and deaths ( 16 ). In addition, traveling and population dispersal can aggravate the spread of disease in each region ( 17 , 18 ). Although air travel has clearly been a major driver of the pandemic, intercontinental travel restrictions were less effective between Europe and the USA ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…The value of p can be obtained by substituting the values of m and s from ( 9) and ( 10), respectively, into (11). Further, it can be observed that only three samples are sufficient to get a Gaussian wave.…”
Section: Estimation Of Mean Standard Deviation and The Peak Value Of A Gaussian Wavementioning
confidence: 99%
“…The mu variant is also monitored. A few variants of COVID-19 frequency in limited and unrestricted areas have been suggested in studies [7][8][9][10][11][12][13][14][15][16][17][18][19][20]23].…”
Section: Introductionmentioning
confidence: 99%